EFFECT OF LIQUIDITY, PROFITABILITY, LEVERAGE, FIRM SIZE AND SALES GROWTH ON FINANCIAL DISTRESS OF PROPERTY AND REAL ESTATE COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE - ,; ,; ,; ,; ,; , (Bilancia : Jurnal Ilmiah Akuntansi; Vol 8 No 4 (2024): Bilancia : Jurnal Ilmiah Akuntansi, 2024)
This study aims to find out and analyze the influence of liquidity, profitability, leverage, firm size, and sales growth on the financial distress of property and real estate sector companies   listed on the Indonesia Stock Exchange during 2017-2021. The data analysis technique of this study uses descriptive analysis and logistic regression analysis with the help of SPSS statistical software version 21. The population of this study is property and real estate sector companies listed on the Indonesia Stock Exchange during 2017-2021. The sample used in this study is 46 companies in the property and real estate sector listed on the Indonesia Stock Exchange during 2017-2021. The sample determination uses the purposive sampling method and the data analysis technique used is logistic regression. The Independent Variables are liquidity, profitability, leverage, firm size, and sales growth which are tested for their effect on financial distress as dependent variables. The results of this study show that liquidity and profitability have a positive effect on financial distress, while firm size has a negative effect on financial distress. On the other hand, leverage and firm size have not been shown to have a significant effect on financial distress. Penelitian ini bertujuan untuk mengetahui dan menganalisis pengaruh likuiditas, profitabilitas, leverage, firm size, sales growth terhadap financial distress perusahaan sektor property dan real estate yang terdaftar di Bursa Efek Indonesia selama tahun 2017-2021. Teknik analisis data penelitian ini menggunakan analisis deskriptif dan analisis regresi logistik dengan bantuan software statistic SPSS versi 21. Populasi penelitian ini adalah Perusahaan sektor property dan real estate yang terdaftar di Bursa Efek Indonesia selama tahun 2017-2021. Sampel yang digunakan dalam penelitian ini adalah 46 perusahaan sektor property dan real estate yang terdaftar di Bursa Efek Indonesia selama tahun 2017-2021. Penentuan sampel menggunakan metode purposive sampling dan teknik analisis data yang digunakan adalah regresi logistik. Variabel Independen adalah likuiditas, profitabilitas, leverage, firm size, sales growth yang diuji pengaruhnya terhadap financial distress sebagai variabel dependen. Hasil penelitian ini menunjukkan bahwa likuiditas dan profitabilitas berpengaruh positif terhadap financial distress , sedangkan firm size berpengaruh negatif terhadap financial distress . Di sisi lain, leverage dan firm size tidak terbukti memiliki pengaruh yang signifikan terhadap financial distress .